Detection of natural infection of infectious spleen and kidney necrosis virus in farmed tilapia by hydroxynapthol blue-loop-mediated isothermal amplification assay - R. Suebsing (2018)
© 2016 The Society for Applied Microbiology Aims: Infectious spleen and kidney necrosis virus (ISKNV) has recently been recognized as a causative agent of serious systemic disease in tilapia. Our objective was to establish a new colorimetric loop-mediated isothermal amplification (LAMP) assay with pre-addition of hydroxynapthol blue (blue-LAMP) to investigate ISKNV transmission in tilapia. Methods and Results: The blue-LAMP, targeting a major capsid protein gene of ISKNV, was conducted at 65°C for 45 min, allowing unaided visual detection of the pathogen based on colour change without cross-amplification of other known fish pathogens tested. Comparison of blue-LAMP and PCR assays revealed a higher detection level for blue-LAMP assay (41·33%) in a population of farmed tilapia infected with ISKNV. The investigation of ISKNV transmission pattern in farmed red tilapia using the blue-LAMP revealed a possible matroclinical form. The presence of ISKNV in the gonad samples was confirmed by in situ LAMP assay. Positive signals only appeared in ovarian follicles, and not in oocytes. Moreover, tissue tropism assay revealed that the brain was the main target organ in both farmed red tilapia (40%) and Nile tilapia (20%). Conclusions: The developed blue-LAMP assay has the potential to be used as a viable tool for screening covert and natural infections of ISKNV in tilapia. The evidence of vertical transmission of ISKNV infection in tilapia indicates the seriousness of this disease and will require a close attention and collaboration between tilapia hatcheries and disease experts in order to find a solution. Significance and Impact of the Study: The new blue-LAMP assay is a time-saving and economically viable detection tool, which allows unaided visual detection for ISKNV in tilapia, and it could be applicable for field applications. Evidence on the vertical transmission of ISKNV in farmed tilapia suggests a need for developing farm management practices to control the spread of virus in aquaculture industries.